Impact and countermeasures of generative AI represented by ChatGPT on the telecom industry - Sihong ZHANG; Jian ZHANG (Dianxin kexue)
The release of ChatGPT, sparked a wave of generative AI, representing the arrival of the singularity moment of general artificial intelligence and highly likely restructuring the information industry ecosystem.The domestic industry has strengthened the research in the field of intelligent computing represented by ChatGPT, and operators have become the main force in the construction of computing network infrastructure, ushering in new opportunities for the development of intelligent computing.A detailed analysis of the capabilities, development status, and application prospects of generative AI were provided, and the technical elements behind generative AI, the demands for computing network resources, the impact on the communication industry, the opportunities and challenges faced by operators in the development wave of generative AI were thought about.Finally, the positioning and response strategies of operators were discussed.